Productivity-enhancing reallocation during the Covid-19 pandemic - Tibor Lalinsky; Jaanika Meriküll; Paloma López-García (European Central Bank (ECB), 2024)
This paper studies how the Covid-19 pandemic and the extensive job retention support that accompanied it affected productivity in Europe. The focus is on the reallocation channel and productivity-enhancing reallocation of jobs, following Foster et al., 2016. An extensive micro-distributed analysis of firm-level data for 11 euro area countries is used. The unique firm-level datasets are constructed by merging balance-sheet and income-statement data with policy support data. The paper exploits variation in employment responsiveness to productivity over time, particularly examining the relationship between changes in employment responsiveness and the job retention support in 2020 and studying how well the support was targeted by firm productivity. Acknowledging limitations of a small set of countries covered and occasionally large confidence bounds around estimates, the findings suggest that (1) productivity-enhancing reallocation was weaker in the pandemic than in the Great Recession; (2) The countries that were more generous with job retention support and countries where more support was allocated to low-productivity firms showed weaker productivity-enhancing reallocation in 2020.
Keywords: D22; H25; J38; L29; 330; Productivity-enhancing reallocation; Covid-19; adjustment of firms; job retention support; cross-country analysis